Edward Elgar and the First World War: An Exploration of the Reception History of His Wartime Music - Temple, Katie Victoria (2021)
Edward Elgar offers an interesting case study in the British cultural response to the First World War. By the time of the conflict, Elgar’s reputation as an important national figure was firmly established; as such, his music became part of the official ‘war effort’. Despite this, many of his wartime compositions have failed to obtain a permanent place in the concert repertoire, with this music often seen as necessary for the time but insignificant in comparison to the rest of his output.